A imagem como instrumento de identidade – A figuração de São Jerónimo no manuscrito Bíblico ANTT, Lorvão 45 - Inês Correia (Medievalista)
Our discussion focuses on the image of the 'Scribe' that fills the first initial of a 13th century Bible, Ms. ANTT, Lorvão 45. It reflects an exercise of analysis based on Panofsky's method, but complemented by the vision of image as a possible result of multiple meaning, applied by Jean Wirth as hybrid iconography.Several 'Scribe' images, from Bibles of the same period, are compared with earlier ones, in order to achieve a deliberate iconographic system, which relates the Scribe (as scriptor) with Jerome (Doctor of the Church).